2009
DOI: 10.1186/1471-2334-9-67
|View full text |Cite
|
Sign up to set email alerts
|

Direct susceptibility testing for multi drug resistant tuberculosis: A meta-analysis

Abstract: BackgroundOne of the challenges facing the tuberculosis (TB) control programmes in resource-limited settings is lack of rapid techniques for detection of drug resistant TB, particularly multi drug resistant tuberculosis (MDR TB). Results obtained with the conventional indirect susceptibility testing methods come too late to influence a timely decision on patient management. More rapid tests directly applied on sputum samples are needed. This study compared the sensitivity, specificity and time to results of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
5
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 35 publications
9
107
5
10
Order By: Relevance
“…Chaiyasirinroje et al analyzed 202 sputum samples of clinically diagnosed TB patients with MODS assay in relation to gold standard BACTECT MGIT 960 and Ogawa solid culture. The median time to culture positivity by MODS, solid, and liquid culture were 12, 30, and 6 days, respectively [15]. In another study conducted in Egypt, 115 smearpositive TB patients were simultaneously tested using MODS and the BACTECT MGIT 960.…”
Section: Isolation and Culturementioning
confidence: 99%
“…Chaiyasirinroje et al analyzed 202 sputum samples of clinically diagnosed TB patients with MODS assay in relation to gold standard BACTECT MGIT 960 and Ogawa solid culture. The median time to culture positivity by MODS, solid, and liquid culture were 12, 30, and 6 days, respectively [15]. In another study conducted in Egypt, 115 smearpositive TB patients were simultaneously tested using MODS and the BACTECT MGIT 960.…”
Section: Isolation and Culturementioning
confidence: 99%
“…The utility of Alamar Blue as a phenotypic high-throughput cell viability screen for identification of potentially new TB leads for screening of clinical isolates of MTB has been demonstrated [23,24], among others. In addition, several studies have also shown the reliability of Alamar blue cell viability assay for detection of drug resistant MTB [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…The resazurin microtiter assay (REMA) was performed in 7H9 medium containing Middlebrook broth and 0.5% glycerol and supplemented with oleic acid, albumin, dextrose, and catalase (Difco TM ) as previously reported [23][24][25]. Clear 96-well plates were inoculated with 100 μL of drug diluted with 90 µl of 7H9 medium and 10 µL DMSO (giving essentially 50 µL of drug).…”
Section: Biologymentioning
confidence: 99%
“…For detecting rifampin resistance, the Genotype MTBDRplus assay shows a diagnostic sensitivity of approximately 98% with a specificity of approximately 99%. 41 In contrast, for detecting isoniazid resistance the diagnostic sensitivity is only approximately 84% with about the same specificity (approximately 100%). 41 The reason for the lower sensitivity in detecting isoniazid resistance compared with detecting rifampin resistance isn't completely understood, but may, in part, be that the assay tests for fewer genes conferring resistance to isoniazid resistance compared with the number of genes that can be detected conferring resistance to rifampin.…”
Section: Line Probe Assaysmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42] Conceptually similar to the INNO-Lipa Rif.tb assay, the MTBDRplus assay has been reported to have a diagnostic sensitivity of approximately 94% for detecting M tuberculosis DNA in smear-positive respiratory specimens. 33 It is of interest that most clinical evaluations of this device have focused on its use for susceptibility testing, not detection of M tuberculosis, so the performance characteristics for the latter use are less well defined.…”
Section: Line Probe Assaysmentioning
confidence: 99%